What Is the Profile of Overweight Individuals Who Are Unsuccessful Responders to a Low-Energy Diet? A PREVIEW Sub-study - Tremblay, Angelo; Fogelholm, Mikael; Jalo, Elli; Westerterp-Plantenga, Margriet S.; Adam, Tanja C.; Huttunen-Lenz, Maija; Stratton, Gareth; Lam, Tony; Handjieva-Darlenska, Teodora; Handjiev, Svetoslav; Martinez, J. Alfredo; Macdonald, Ian A.; et al. (Frontiers in Nutrition, 2021)
This study was performed to evaluate the profile of overweight individuals with pre-diabetes enrolled in PREVIEW who were unable to achieve a body weight loss of ≥ 8% of the baseline value in response to a two-month low-energy diet (LED). Their baseline profile reflected potential stress-related vulnerability that predicted a reduced response of body weight to a LED programme. The mean daily energy deficit maintained by unsuccessful weight responders of both sexes was less than the estimated level in successful female (656 vs 1299 kcal, p < 0.01) and male (815 vs 1659 kcal, p < 0.01) responders. Despite this smaller energy deficit, unsuccessful responders displayed less favorable changes in susceptibility to hunger and appetite sensations. They also did not benefit from the intervention regarding the ability to improve sleep quality. In summary, these results show that some individuals display a behavioral vulnerability which may reduce the ability to lose weight in response to a diet-based weight loss program. They also suggest that this vulnerability may be accentuated by a prolonged diet restriction.